En jämförelse av sitkagranens (Picea sitchensis) och den vanliga granens (P. abies) produktion - Tengberg, Fredrik (SLU/Southern Swedish Forest Research Centre, 2005)
Sitka spruce (Picea sitchensis) is a tree species that have its natural distribution along the West Coast of North America, from Alaska in the north to northern California in the south. Sitka spruce is a typical coastal tree species that can reach heights up to 85 meters and occurs in single pure as well as in mixed stands. The main purposes of this study were to describe the Sitka spruce growing characteristics and the volume production in comparison to spruce (Picea abies). The possibility to predict future volume production by using prognosis tools designed to be used on spruce were also studied. The material that has been used in this study are permanent sitka trials established by the Faculty of Forestry fixed Sitka trials and also material gathered in this study. A literature study was also carried out in order to determine the Sitka spruce growing characteristics. Sitka spruce has a high adaptation and a high volume production on a broad scale of soil types. The tree species is a pioneer species that has a fast early growth and in combination with sharp needles it is less susceptible to animal browsing than spruce. The factor that is the single most limiting factor for where the Sitka spruce can be planted is frost. This factor can be limited by using plant material with a well-suited provenance. According to the literature, the Sitka spruce has an average total volume production that is between 20-40% higher than spruce. The result in this study indicate that the average difference in total volume production were 14% higher for Sitka, on soils with the same site index. There were a big distribution in the results and if only the three best stands were studied the average Sitka spruce total volume production were approximately 30% higher than for the comparable spruce stands. The origin of plant materials has a big impact on production level and in those cases were the Sitka spruce production is below the spruce production, there are strong evidence that the Sitka spruce is represented by a poor material. By using prognosis tools, designed for spruce stands, the possibility to predict future production in Sitka stands were studied and compared. The prognosis tool that were used were ProdMod (Production Model) and height increment curves for spruce (Eriksson, 1976). The prognosis that gave the best result were when the two prognosis tools were combined. The results from this study shows that the prognosis underestimated the average volume production with approximately 3%. This indicates that there are good possibilities to predict future volume production by using prognosis tools intended to be used for spruce stands. When the top height increment were compared between the two tree species the Sitka spruce had a more durable height increment than spruce.